2007
DOI: 10.1007/s10549-007-9655-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in the vascular endothelial growth factor gene and breast cancer risk. The Austrian “tumor of breast tissue: incidence, genetics, and environmental risk factors” study

Abstract: Our findings do not support the hypothesis that VEGF polymorphisms are associated with breast cancer risk. The association of the VEGF -634C allele with small tumor size is in clear contrast to a previous publication and should be interpreted with caution until replicated by additional studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
51
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 19 publications
(24 reference statements)
10
51
6
Order By: Relevance
“…With regards to rs1570360 or rs3025039, our results indicate no significant associations with breast cancer characteristics, which appear to corroborate previous reports either for rs1570360 23,42 or rs3025039. 23,26,30,42,45 In relation to rs2010963, however, our lack of significant associations with histopathological features of breast cancer contradicts previous studies, which have indicated that patients with the variant CC 23,35,42 or GC genotypes 44 have larger tumor size (> 20 mm),if compared to those with the major GG genotype. Luo et al 35 also found positive association between the variant homozygous CC genotype of rs2010963 and high histological grade, whereas Sa-Nguanraksa et al 44 found positive associations for the GC genotype with perineural invasion and advanced tumor stage (II-IV).…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…With regards to rs1570360 or rs3025039, our results indicate no significant associations with breast cancer characteristics, which appear to corroborate previous reports either for rs1570360 23,42 or rs3025039. 23,26,30,42,45 In relation to rs2010963, however, our lack of significant associations with histopathological features of breast cancer contradicts previous studies, which have indicated that patients with the variant CC 23,35,42 or GC genotypes 44 have larger tumor size (> 20 mm),if compared to those with the major GG genotype. Luo et al 35 also found positive association between the variant homozygous CC genotype of rs2010963 and high histological grade, whereas Sa-Nguanraksa et al 44 found positive associations for the GC genotype with perineural invasion and advanced tumor stage (II-IV).…”
Section: Discussioncontrasting
confidence: 92%
“…Our finding of a positive association between variant rs699947 genotypes and high-grade tumors is in opposite direction of that reported by Jin et al, 23 who found an association between variant homozygous AA and low-grade tumors, whereas other authors reported no association between rs699947 and tumor grade. 37,45,46 Likewise, the results indicating positive association of variant genotypes of rs833061 with high histological grade and lymph node metastases at diagnosis also appear to contradict those of Sa-Nguanraksa et al, 44 who reported lower lymphovascular invasion of breast tumors with the variant homozygous genotype CC. The impact of rs833061 in breast cancer has also been studied by Rahoui et al, 37 who found no significant associations with histopathological features.…”
Section: Discussionmentioning
confidence: 78%
“…Association of CC genotype of +936C/T polymorphism has been reported with tumor aggressiveness in Swedish breast cancer patients (Jin et al, 2005). The +405C allele has also been reported to associated with small breast tumor size in Austrian population (Langsenlehner et al, 2008). The findings of present study indicated a significant association of VEGF +936C>T and +405C>G polymorphisms with the increased breast cancer risk in Punjab.…”
Section: Discussionsupporting
confidence: 62%
“…Combined +405CC+CG genotype has been associated with higher susceptibility for Prostate (Sfar et al, 2006), gastric (Guan et al, 2009) and small cell lung carcinoma in males (Zhai et al, 2008a). Whereas, no association of VEGF +405C>G polymorphism was observed in Swedish (Jin et al, 2005), Chinese (Kataoka et al, 2006;Luo et al, 2013) and Austrian (Langsenlehner et al, 2008) breast cancer patients. A study from North India on Kashmiri lung cancer patients did not show any significant difference in genotype distribution of +405C/G polymorphism between cases and controls (Naik et al, 2012).…”
Section: Discussionmentioning
confidence: 76%
“…VEGF-A is highly polymorphic in the promoter and 5¢ untranslated region and single-nucleotide polymorphisms in this region have been reported to regulate VEGF expression via alternative initiation of transcription and internal initiation of translation (Akiri et al, 1998;Huez et al, 1998). Polymorphisms of VEGF have been studied with disparate results in various diseases like type 2 diabetes (Awata et al, 2002;Buraczynska et al, 2007), giant cell arteritis (Rueda et al, 2005), renal complications in Henoch-Schonlein purpura (Rueda et al, 2006), hepatocellular carcinoma (HCC) (Kong et al, 2007), prostate cancer (Onen et al, 2008), familial endometriosis (Zhao et al, 2008), ectopic pregnancy (Elito et al, 2010), glomerulonephritides (Safrankova et al, 2011), hypertension (Kim et al, 2012), age-related macular degeneration (Lu et al, 2012), and breast cancer (Lu et al, 2005;Jacobs et al, 2006;Langsenlehner et al, 2008;Schneider et al, 2008;Rodrigues et al, 2012).…”
mentioning
confidence: 99%